Neck pain and migraine: Association or cause?—A narrative review of the literature. Issue 1 (2nd April 2019) - Albisser, Arlette; Le Clec'h, Yann; Sprott, Haiko
This literature review deals with the question whether neck pain (NP) constitutes a symptom or a trigger of migraine. Firstly, a short survey about some techniques for measuring NP in association and relation with migraine is presented. Secondly, the arguments about NP as a symptom or a trigger of migraine are being reviewed and compared. The main questions are the following: Which tests can be used to distinguish NP as a trigger or a symptom of migraine? Is a therapy for NP an adequate method to treat migraine? Finally, the pros and cons of NP as a symptom or as a trigger will be reviewed, and possible treatment options will be suggested. This review found that no reliable and standardized tests exist to classify NP in relation to migraine. However, there is a comparability among these studies due to the common use of migraine definition in the "International Classification of Headache Disorders." Regarding the quality and methods, different types of studies were analyzed, for example, retrospective, prospective, and cross-sectional studies. Nevertheless, none of these types are specifically suited to show a causality between NP and migraine. In order to do this, the authors would suggest using a randomized controlled study. Another adequate study design might be a population-based case–control crossover study and calculating the population attributable risk. Furthermore, the pathophysiology of NP in migraine patients should be investigated in more detail. Besides their questionable suitability for showing a connection between NP and migraine, some studies were additionally subject to a population and selection bias. To sum up, part of the authors in the reviewed literature generate the hypothesis that NP is more often a symptom than a trigger of migraine. However, due to methodological flaws, more studies are necessary to confirm this hypothesis.